Prevalência de disfunção temporomandibular em adolescentes da Regional Centro-Sul da cidade de Belo Horizonte: um estudo epidemiológico - Roberto Brigido de Nazareth Pedras (2010)
The main objective of this project is to determine the prevalence of the Diagnosis of Temporomandibular Disorders (TMD) and check the association with age, gender, type of school, and social vulnerability index in regional south-central subdivision in Belo Horizonte city. This cross-sectional study was conducted in a convenience sample consisted of 143 schoolchildren between the ages from 15 and 20 years old of public and private institutions of elementary and secondary education in regional center-south subdivision in Belo Horizonte. The Research Diagnostic Criteria for TMD (RDC / TMD) was used to evaluate the diagnosis of TMD by a trained examiner (Kappa Intra = 0.7683) and for the socioeconomic classification was used social vulnerability index (SVI) and type of school. Those data were analyzed SPSS for Windows, version 17. Descriptive and bivariate analyzes were performed using the Qui-Quadrado test (p <0,05). From the sample score it was realized that 82.5% (118) studies in public schools, and 71.3% (102) individuals were female. The diagnosis of TMD was present in 44.1% (63) of the sample. The most common diagnosis found on the group was on muscle disorders, corresponding to 28.7% (41) of the examined adolescents, followed by disc displacement , with 18.9% (27). Myofascial pain was diagnosed in 25.2% (16) of the individuals participating in the study. Those TMD are not statistically associated to gender (p = 0.44), age (p = 0.86), type of school (p = 0 , 37), or social vulnerability (p = .69). We conclude that the prevalence of TMD in this sample was high, and was not associated with gender, age or socioeconomic conditions.